THE EFFECT OF COSMETICS RETAIL CHAIN STORESâ€™ ATTRIBUTES ON CONSUMER CHOICE IN LITHUANIA - Elena Salamandic; Sonata AlijoÅ¡ienÄ—; Rasa GudonaviÄienÄ— (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose, 2016)
The current research paper aims to determine the store attributes behind the consumer preference when choosing a cosmetics retail chain store in Lithuania. The authors conduct a survey analysis across a random sample of consumers to test the impact of ten store attributes on consumers’ choice. The store attributes are divided in two categories: image and economic attributes. The authors use the distribution of the store attributes in two ways: to distinguish image and economic factors marginally and to draw positioning maps for all market players. The respondents evaluated each store attribute in focus on a Likert scale. Weighted averages were drawn to rank the attributes according to their importance. In the further analysis, the store attributes ranking was performed for each research object separately. This information helped the authors to perform a positioning analysis in order to get the final results of marginal evaluation of all cosmetics retail chain stores in question. The research objects were positioned on a map that evaluates their performance on image and economic factors. The plot analysis helped to depict the marginal differences between the stores. The empirical analysis revealed that 4 out of 10 store attributes, namely product assortment, discounting system, service quality and shopping experience, were ranked as the most important influencers of consumer choice. The insights derived from the analysis results provide the grounds on which marketing managers can derive recommendations about the improvement of brand awareness, image and position statements of the retailers in focus.